The Role of Model-View Controller in Object Oriented Software Development - Thakur, Ram Naresh; Pandey, U.S. (Nepal Journal of Multidisciplinary Research, 2019)
Object Oriented Software Development (OOSD) is a design technique that is used before the development and design of a software. This design method makes the system appears as a collection of objects to communicate with other objects by passing messages. The Model-View-Controller (MVC) has been inherited from Object-Oriented Programming (OOP) with the integration of Graphical User Interface (GUI) and interactive program execution. The MVC is very useful for developing Interactive and Dynamic Web Applications and iOS. With MVC, developers can trust on design patterns that are widely accepted as solutions for recurring problems. MVC can be used to develop flexible, reusable and modular Software. Applying the MVC design pattern in object-oriented Software development a flexible, reliable, modular and scalable website can be built. So, it’s necessary for every developer to have the knowledge of software development using MVC design pattern.